2020
DOI: 10.13060/csr.2020.021
|View full text |Cite
|
Sign up to set email alerts
|

Individual Experiences of Surveillance: Attitudes towards Camera Surveillance in Slovakia

Abstract: After the fall of the communist regime, Slovakia saw the introduction and subsequent rapid growth of camera surveillance, particularly around the turn of the millennium. These developments occurred in a specific political, cultural, and historical context, which affects perceptions of and reactions to surveillance by individual citizens. The post-communist context is characterised by relatively low levels of resistance to the introduction of various technological surveillance mechanisms, including the rapid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…As previous research has suggested, this does not mean that the acceptance of these technologies is universal and unconditional (Kovanič 2020).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As previous research has suggested, this does not mean that the acceptance of these technologies is universal and unconditional (Kovanič 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Three respondents also mentioned other potential positive consequences of cameras, such as security in and around apartment blocks and services (such as those providing information about traffic). A low level of privacy concern was connected with trust in the effectiveness of cameras, which led to their higher acceptance (Kovanič 2020). If there was any concern about CCTV in public spaces, it did not relate to the kind of surveillance but rather its extent: one respondent described a situation where there were too many cameras as "depressing" (R4, FG3).…”
Section: A Non-controllable Public Spacementioning
confidence: 99%
“…One of the primary characteristics of some contemporary surveillance technology such as CCTV is its mass character (Kovanič 2020), which is evidenced by the continuously expanding and prolific presence of open-street camera surveillance systems across the globe. According to Norris & Armstrong (1997;, mass surveillance is unlike targeted, personalized surveillance as it is often automated, involuntary, nondiscriminatory, and routinized.…”
Section: Growth Of Cctvmentioning
confidence: 99%
“…According to Norris & Armstrong (1997;, mass surveillance is unlike targeted, personalized surveillance as it is often automated, involuntary, nondiscriminatory, and routinized. CCTV camera surveillance falls into the category of mass surveillance as it targets all individuals who move within its range of coverage (Kovanič 2020); however, targeting all people within the gaze does not mean that individuals will be treated equally 12 . argues that this rise of cameras has helped to transform western societies into surveillance societies, as visual surveillance technologies such as CCTV have important implications for social relations and modes of governance.…”
Section: Growth Of Cctvmentioning
confidence: 99%
See 1 more Smart Citation